Digital health interventions in reducing loneliness and improving mental health in older adults - a literature review - Jakub Kołacz; Patrycja Oleś; Marcin Kwiatkowski; Tomasz Koziński; Marta Donderska; Paulina Bochniak; Mateusz Bryła; Zofia Bryła; Monika Spaczyńska-Kwiatkowska; Tomasz Włoch (Journal of Education, Health and Sport)
Introduction: Loneliness remains a concerning health issue, especially among the older population. It leads to numerous negative psychological and physiological negative health outcomes. Digital health interventions have presented themselves as promising strategies for mitigating loneliness and improving mental health in this demographic group.